STRATEGY FOR OBTAINING UNQUALIFIED AUDIT OPINION (WTP) THROUGH ACCOUNTING CONSERVATISM - Yuni Sukandani; Siti Istikhoroh (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to analyze the strategies undertaken by companies going public in order to obtain Unqualified Audit Opinions (WTP) through the principle of accounting conservatism. A WTP opinion is obligatory for agencies to make certain reporting transparency and duty according with Financial Accounting Standards. The studies facts is taken from the Financial Statements of Food and Beverage Companies indexed at the Indonesia Stock Exchange for the period 2018 to 2021. Several independent variables are predicted to influence conservatism, namely debt covenants, growth opportunities, profitability, and political costs, and are analyzed using Linear Regression analysis Double. An analysis of the use of conservatism as a strategy to obtain an unqualified audit opinion is carried out in a descriptive analysis on inventory accounts and depreciation of fixed assets. The outcomes of the evaluation show that every one the anticipated impartial variables have a vast impact on conservatism. While the use of the principle of conservatism to obtain WTP audit opinions is carried out by applying various accounting methods that produce the least profit, namely the LIFO method in recording inventories, maximizing the economic life of fixed assets and then depreciating them using the straight-line method. This research is useful theoretically and practically. At the theoretical level, the research results are able to contribute ideas to academics to understand the practice of conservatism in companies going public. While practically, the research results are useful as a basis for making investment decisions. Prospective investors need to pay attention to the WTP opinion issued by the external audit by analyzing the relationship between the amounts between accounts in the financial statements.